1993
DOI: 10.1139/x93-085
|View full text |Cite
|
Sign up to set email alerts
|

Breeding objectives for pulp production of Eucalyptusglobulus under different industrial cost structures

Abstract: Breeding objectives were defined for pulp production of Eucalyptusglobulus Labill, using a simple profit equation relating the monetary cost savings per tonne of pulp produced with stem volume, wood density, and pulp yield. The economic importance of each trait was calculated for five different pulp and forestry industry scenarios with widely different cost structures. Selection indices integrating various combinations of volume growth, wood density, and pulp yield were compared for their ability to meet the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 0 publications
5
70
0
2
Order By: Relevance
“…Examples for wood density should demonstrate the large differences obtained in open-pollinated progeny trial studies. For E. globulus Borralho et al (1993) reported a genetic gain of 47% for E. regnans, while Raymond et al (1998) reported 3.5%wood density. The latter study also reports a genetic gain for fibre length as high as 6.8%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Examples for wood density should demonstrate the large differences obtained in open-pollinated progeny trial studies. For E. globulus Borralho et al (1993) reported a genetic gain of 47% for E. regnans, while Raymond et al (1998) reported 3.5%wood density. The latter study also reports a genetic gain for fibre length as high as 6.8%.…”
Section: Discussionmentioning
confidence: 97%
“…From extracted and air-dried samples wood density and microfibril angles (MFAs) were determined and weighted by the cross-sectional area at each measured tree height (Downes et al, 1997;Evans, 1994;Evans et al, 1995). Dry wood consumption (WC in m 3 /t), which is the volume of wood required to produce a tonne (dry) of pulp, was calculated according to Borralho et al (1993). WC can be estimated as the inverse of the product of wood density (kg dry wood / m 3 ) and pulp yield (kg dry pulp/kg dry wood):…”
Section: Methodsmentioning
confidence: 99%
“…Selection of individuals for establishment in a clonal seed orchard using an index 254 that combines growth and wood quality traits requires index weightings for each trait; 255 these weights can be deduced using a variety of methods (Borralho et al 1993, 256 Greaves et al 1997. In this study, the approach used to compare selection index 257 weights relies on the ability to use relative weightings since standing-tree pulp 258 productivity is calculated as the product of the three selection traits: volume, density 259 and Kraft pulp yield.…”
Section: Selection Index Weights 253mentioning
confidence: 99%
“…High basic density is desired for kraft pulp [8,14] and most solidwood products [5,29,42], the presence of decay or kino can result in degrade in solidwood products [2][3][4] and timber exhibiting high shrinkage angle is likely to be more prone to drying degrade. Suboptimal expression of these traits in the lower stem disproportionately affects whole-tree economic value because the lower stem represents a high proportion of total stem volume and produces logs of the largest diameter.…”
Section: Longitudinal Variationmentioning
confidence: 99%